2019
DOI: 10.1016/j.cognition.2019.104014
|View full text |Cite
|
Sign up to set email alerts
|

Sensory cue combination in children under 10 years of age

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that: • a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 44 publications
(91 reference statements)
2
20
0
Order By: Relevance
“…Indeed, feedback has been shown to be vital in the development of sensory integration and calibration; children can learn to integrate sensory cues only when they receive feedback about their judgments (Negen et al, 2019), and delaying feedback inhibits sensorimotor recalibration in children (Vercillo, Burr, Sandini, & Gori, 2015). Also, and in comparison to the multisensory development literature, many studies have shown that the ability to integrate and segment basic visual features, motion, and patterns develops very early in life (for review, see Braddick & Atkinson, 2011).…”
Section: Blanking Effect and The Development Of Integration In Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, feedback has been shown to be vital in the development of sensory integration and calibration; children can learn to integrate sensory cues only when they receive feedback about their judgments (Negen et al, 2019), and delaying feedback inhibits sensorimotor recalibration in children (Vercillo, Burr, Sandini, & Gori, 2015). Also, and in comparison to the multisensory development literature, many studies have shown that the ability to integrate and segment basic visual features, motion, and patterns develops very early in life (for review, see Braddick & Atkinson, 2011).…”
Section: Blanking Effect and The Development Of Integration In Childrenmentioning
confidence: 99%
“…Integration of different visual features such as stereo and motion or texture, which has been found to occur in adults (Johnston, Cumming, & Landy, 1994;Knill & Saunders, 2003), may be slower to develop, as depth processing is calibrated to account for the changing position of the eyes in a growing head, in a manner similar to how integration of visuohaptic information relies on the calibration of the developing haptic system (Ernst, 2008;Gori et al, 2008). Adults can learn novel cue combination within a few hours (Negen, Wen, Thaler, & Nardini, 2018), suggesting that the slow development of multisensory cue combination may be limited by biological development (Negen et al, 2019).…”
Section: Blanking Effect and The Development Of Integration In Childrenmentioning
confidence: 99%
“…The Bayesian model of multisensory integration suggests that adults fuse redundant sensory inputs in a statistically optimal way by weighting the sources according to their uncertainty 16 , 17 . The ability to combine different cues to obtain more precise estimates of one's surroundings appears late in childhood development 18 , 19 , that is, after the individual modalities have matured 20 , 21 , unless additional feedback on the reliability of each cue is provided 22 . Younger children will thus favor the information provided by the modality with the highest context-dependent reliability 19 , 23 .…”
Section: Introductionmentioning
confidence: 99%
“…They do not use a Bayesian process when given landmark and self-motion cues (Nardini et al, 2008). Children under 10 generally do not use multiple cues in a Bayesian manner ; though see Negen et al, 2019).…”
Section: Interim Discussionmentioning
confidence: 99%